THE OXIDATION STATES OF COPPER AND IRON IN MINERAL SULFIDES, AND THE OXIDES FORMED ON INITIAL EXPOSURE OF CHALCOPYRITE AND BORNITE TO AIR - Goh S.W.; Buckley A.N.; Lamb R.N.; Rosenberg R.A.; Moran D. (My University, 2006)
Metal L2,3, sulfur K and oxygen K near-edge X-ray absorption fine structure (NEXAFS) spectra for chalcopyrite, bornite, chalcocite, covellite, pyrrhotite and pyrite have been determined from single-piece natural mineral specimens in order to assess claims that chalcopyrite should be regarded as CuIIFeIIS2 rather than CuIFeIIIS2, and that copper oxide species are the principal initial oxidation products on chalcopyrite and bornite exposed to air. Spectra were obtained using both fluorescence and electron yields to obtain information representative of the bulk as well as the surface. Where appropriate, NEXAFS spectra have been interpreted by comparison with the densities of unfilled states and simulated spectra derived from ab initio calculations using primarily the FEFF8 code and to a lesser extent WIEN2k. Metal 2p and S 2p photoelectron spectra excited by monochromatised Al Kα X-rays were determined for each of the surfaces characterised by NEXAFS spectroscopy. The X-ray excited Cu LMM Auger spectrum was also determined for each copper-containing sulfide. FEFF8 calculations were able to simulate the experimental NEXAFS spectra quite well in most cases. For covellite and chalcocite, it was found that FEFF8 did not provide a good simulation of the Cu L3-edge spectra, but WIEN2k simulations were in close agreement with the experimental spectra. Largely on the basis of these simulations, it was concluded that there was no convincing evidence for chalcopyrite to be represented as CuIIFeIIS2, and no strong argument for some of the Cu in either bornite or covellite to be regarded as Cu(II). The ab initio calculations for chalcopyrite and bornite indicated that the density of Cu d-states immediately above the Fermi level was sufficient to account for the Cu L3-edge absorption spectrum, however these incompletely filled Cu d-states should not be interpreted as indicating some Cu(II) in the sulfide structure. It was also concluded that the X-ray absorption spectra were quite consistent with the initial oxidation products on chalcopyrite and bornite surfaces being iron oxide species, and inconsistent with the concomitant formation of copper-oxygen species. © 2006 Elsevier Inc. All rights reserved.